PENGARUH EARNINGS MANAGEMENT TERHADAP CAUSAL DISCLOSURE - Eri Nurjanah; Marsono Marsono (Diponegoro Journal of Accounting, 2013)
Initial Public Offering (IPO) is one reason for the emergence of earnings management is done to attract potential investors. Earnings management is suspected causal disclosure influence as a form of self-serving attributions. This study aimed to examine the effect of earnings management on the causal disclosure of non-financial firms do IPO in 2008-2011 are listed on the Stock Exchange and Bloomberg. This study uses a quantitative approach using secondary data sources, where the observation method used is purposive sampling. This study uses multiple regression analysis with the assumption of Ordinary Least Square (OLS), which consists of two regression models using the control variable Size, Leverage, Audit Quality, Profitability, Sales Growth, Capital Intensity, Current Ratio, Percentage of Public Shares and Industry Dummy. The results of this study indicate that partial earnings management significantly influence causal disclosure assertive. Control variables that influence the assertive causal disclosure Size, Leverage, Audit Quality, and Profitability. While simultaneously earnings management, Size, Leverage, Audit Quality, Profitability, Sales Growth, Capital Intensity, Current Ratio, Percentage of Public Shares and Industry Dummy influence assertive causal disclosure.